1995
DOI: 10.1016/0268-0033(95)92042-k
|View full text |Cite
|
Sign up to set email alerts
|

Oblique abdominal muscle activity in standing and in sitting on hard and soft seats

Abstract: The activity of the oblique abdominal muscles was investigated with the trunk in unconstrained, symmetrical and static postures. Electromyographic recordings in six healthy subjects revealed that in all subjects the activity of both the internal and the external obliques is significantly higher in unconstrained standing than in supine posture. Activity of the internal oblique was higher than that of the external oblique abdominal. The sacrospinal, gluteus maximus and biceps femoris muscles showed practically n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 16 publications
5
14
0
Order By: Relevance
“…There was no significant difference between right and left muscle activities in all trunk muscles in the resting standing posture. The percentage of the MVC in the IO activity in the resting standing posture was higher than in the other muscles, corresponding well to a previous finding [23]. In both slow and natural movements, only ES muscle activity was significantly enhanced, by approximately 1.5-fold, as compared with in resting standing posture.…”
Section: Resultssupporting
confidence: 87%
“…There was no significant difference between right and left muscle activities in all trunk muscles in the resting standing posture. The percentage of the MVC in the IO activity in the resting standing posture was higher than in the other muscles, corresponding well to a previous finding [23]. In both slow and natural movements, only ES muscle activity was significantly enhanced, by approximately 1.5-fold, as compared with in resting standing posture.…”
Section: Resultssupporting
confidence: 87%
“…In line with our results, Sánchez-Zuriága et al [22], also found more activation of IO muscle during exercises with an oscillatory blade while standing than while sitting upright. Perhaps, this result can partially be explained by the stabilizing effect of the IO on the sacro-iliac joints, in addition to its effects on the lumbar spine [23].…”
Section: Discussionmentioning
confidence: 98%
“…3,29,36 sMVICs were generated for the abdominal muscles using the double leg raise movement due to its high reliability. 3,30 The participants were placed in supine, lying with hips flexed at 45°and knees at 90°.…”
Section: Data Collectionmentioning
confidence: 99%